Pembinaan Kreatifitas Dan Inovasi Perempuan Desa Melalui Pengembangan Pemasaran Produk Unggulan Serta Pengelolaan Keuangan Guna Mewujudkan Produk Berdaya Saing Dan Manajemen Keuangan Di Desa Kelungkung - Edi Irawan; Abdul Salam; Hanifa Sri Nuryani (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
The main objective of this community empowerment activity is to develop superior village products through increasing creative and innovative marketing and financial management. The methods used in this community service activity are tutorial methods, mentoring methods, discussion and evaluation methods. The results achieved from this activity are: (1) Kelungkung Village PKK mothers are able to practice developing creative and innovative marketing skills online through the marketplace, (2) Kelungkung Village PKK mothers are able to operate all-in-one computers in marketing the village's superior products , (3) Kelungkung Village PKK mothers are able to understand business financial management